Temporal dynamics of mesoplanktonic cnidarians in a subtropical estuary: Environmental drivers and possible trophic effects. (5th February 2021) - Teixeira-Amaral, Priscila; Rodrigues de Lemos, Vitória; Muxagata, Erik; Nagata, Renato Mitsuo
Abstract: Planktonic cnidarians are important pelagic predators that occasionally reach extremely high densities. It is important to know how environmental variability affects their abundance and distribution in order to understand the population fluctuations and factors that drive their blooms. Plankton samples collected in the Patos Lagoon Estuary (PLE) during an 8-year period (2009–2017) were analyzed and the mesoplanktonic cnidarian community was quantified. The variability in abundance and composition was associated with environmental variables (temperature, salinity, chlorophyll a, and precipitation). From 234 samples, 23, 861 specimens were classified into 34 taxa, of which 21 were determined at the species level. Liriope tetraphylla and Eucheilota maculata were the most frequent species, while Cnidostoma fallax was the most abundant, reaching ~11, 369 ind. m −3 . The temperature was positively related to richness/diversity, while chlorophyll a did not show a clear influence on the mesoplanktonic community. Under low salinity (<10) the community was characterized by Moerisia inkermanica and C. fallax, while Cunina octonaria and Proboscidactyla ornata were associated with increasing salinity (>25). Liriope tetraphylla and the blooms of C. fallax affected the mesozooplankton community, by drastically reducing copepod density and productivity. Eighteen taxa were considered rare (<10 ind. m −3 ), which highlighted the importance of higher frequency samplings (≤15 days) in long time series (≥8 years) to detect species with short life span. Our results demonstrate a marked influence of hydrological regime on the composition and abundance of planktonic cnidarians in the PLE. Highlights: Planktonic cnidarian community and its temporal dynamics were described for the first time in the Patos Lagoon Estuary, Southern Brazil. Planktonic cnidarian diversity positively correlated with salinity increase; Cnidostoma fallax and Moerisia inkermanica are among the few species that tolerate low salinity periods. Liriope tetraphylla and blooms of Cnidostoma fallax spread through the PLE and adjacent coastal areas, thus affecting local mesozooplankton community and secondary productivity.